UNGKAPAN MARAH DAN UNGKAPAN PUJIAN MASYARAKAT NIAS DI KAKI GUNUNG PADANG - Faula Ismi; Ermanto Ermanto (Faculty of Languages and Arts, Universitas Negeri Padang, 2020)
This study aimed to determine the structure and social function of folklore legend naming Batunabontar Batang Natal district Mandailing Natal district. The method used in this research was descriptive method. The data source of this research was the people who inhabit Batunabontar village, Batang Natal District, Mandailing Natal District. The instrument used in this study was the researcher himself and the informant based on the understanding of the structure and social function of the naming legend of a place. Data collection techniques used in this study were observation by observation and to strengthen the data obtained, direct interviews were carried out to the authorities in research on the Social Structure and Function of the Legend of the Naming of Batunabontar Village, Batang Natal District, Mandailing Natal District. The results of this study indicate that the Social Structure and Function of Naming Legend of Batunabontar Village, Batang Natal District, Mandailing Natal District has a unique history and structure and function in the village. The uniqueness of this Batunabontar makes the writer want to know the importance of the structure and function of the Batunabontar in Batang Natal District, Mandailing Natal Regency.